Outcomes and Worsening Renal Function in Patients Hospitalized With Heart Failure With Preserved Ejection Fraction - Sharma, Kavita; Hill, Terence; Grams, Morgan; Daya, Natalie R.; Hays, Allison G.; Fine, Derek; Thiemann, David R.; Weiss, Robert G.; Tedford, Ryan J.; Kass, David A.; Schulman, Steven P.; Russell, Stuart D. (The American journal of cardiology, 2015)
Heart failure with preserved ejection fraction (HFpEF) has been described as a disease of elderly subjects with female predominance and hypertension. Our clinical experience suggests patients with HFpEF from an urban population are far more heterogenous, with greater co-morbidities and significant inhospital morbidity. There are limited data on the hospitalization course and outcomes in acute decompensated HFpEF. Hospitalizations for acute heart failure at our institution from July 2011 to June 2012 were identified by International Classification of Diseases, Ninth Revision, codes and physician review for left ventricular ejection fraction ≥50% and were reviewed for patient characteristics and clinical outcomes. Worsening renal function (WRF) was defined as creatinine increase of ≥0.3 mg/dl by 72 hours after admission. Hospital readmission and mortality data were captured from electronic medical records and the Social Security Death Index. Of 434 heart failure admissions, 206 patients (47%) with HFpEF were identified. WRF developed in 40%, the highest reported in HFpEF to date, and was associated with higher blood pressure and lower volume of diuresis. Compared to previous reports, hospitalized patients with HFpEF were younger (mean age 63.2 ± 13.6 years), predominantly black (74%), and had more frequent and severe co-morbidities: hypertension (89%), diabetes (56%), and chronic kidney disease (55%). There were no significant differences in 1- and 12-month outcomes by gender, race, or WRF. In conclusion, we found hospitalized patients with HFpEF from an urban population develop a high rate of WRF are younger than previous cohorts, often black, and have greater co-morbidities than previously described.